The Apprentice's Quest - Hunter, Erin (Hunter, Erin. Warriors, a vision of shadows, 2017)
The warrior cat Clans have enjoyed many moons of peace and prosperity--but a dark season approaches, and those days will soon be over. Guided by a mysterious vision, the young apprentice Alderpaw of ThunderClan must go on a dangerous journey ... a journey that may be the Clans' only hope.